EFFECTS OF NATIONALISM IN THE WORLD BY SOCIAL MEDIA - Muhammad Asif, Sumayya Akhter, Dr. Raana Afzal (Pakistan Journal of International Affairs, 2023)
This research examined that nationalist spread nationalism by social media. They are keen to do their work by electronic, print and social media but this research focused on social media uses for spreading nationalism by election campaign, this thesis argued on agenda to getting nationalist’s goal, also demonstrated their strategy, technique, and achievement. For data collection this research used twits, news reports and researches for measuring the facts, Nationalists put their agenda to spread nationalistic approach by many techniques, through case study research found that they used computer algorithms to achieved results. By this analysis the world now aware of nationalistic approach, the world can do more for globalization, for the peace of world the people of world can set one agenda on the globe to protect the world from the effects of nationalism. This research explained how the world scenario is changing from globalization to nationalism, social media acts strongly for this nationalistic world.